Polyethylene composition with improved expansion behavior for blow molding
By adjusting the molecular structure and rheological characteristics of the polyethylene composition, the problem of difficult control of the expansion behavior of the polymer composition in blow molding production is solved, and the product quality improvement and expansion optimization are achieved.
Patent Information
- Application Number
- CN202380063541.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-16
- Filing Date
- 2023-09-13
- Publication Date
- 2025-04-15
AI Technical Summary
During the blow molding production process, the expansion behavior of the polymer composition is difficult to control, resulting in inconsistent quality of the product and excessive expansion.
The expansion behavior and mechanical properties of the parison are optimized by adjusting the molecular structure and rheological properties of the polyethylene composition, such as postpolymerization using a radical initiator.
A good balance between parison expansion and mechanical characteristics is achieved, the gel content is reduced, and the quality consistency of the product is improved.
Smart Images

Figure CN119836441A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a polyethylene composition suitable for producing small articles by blow molding. Background Art
[0002] In WO 2005 / 044866 A1, a method of controlling the flow index and / or molecular weight splitting of a polymer composition is disclosed. In one embodiment, the method of producing a polymer composition comprises: in the presence of a polymerizable monomer, a bimetallic catalyst composition, and at least one control agent, in a single polymerization reactor, incorporating a high molecular weight polymer into a low molecular weight polymer to form the polymer composition; wherein the control agent is added in an amount sufficient to control the level of incorporation of the high molecular weight polymer, the level of the low molecular weight polymer, or both. Examples of control agents include alcohols, ethers, amines, and oxygen.
[0003] In US2012 / 0220747 A1, bimodal polyethylene composition and its manufacturing method are provided. In at least one specific embodiment, the bimodal polyethylene composition may include a high molecular weight component with a weight average molecular weight (Mw) from about 400,000 to about 950,000. The bimodal polyethylene composition may include a low molecular weight component with a weight average molecular weight (Mw) from about 3,000 to about 100,000. The high molecular weight component may be present in an amount within the range of about 25 wt % to about 40 wt % of the bimodal polyethylene composition. The bimodal polyethylene composition may have a die swell percentage less than about 80%.
[0004] A method for modifying polyethylene is described in WO2008 / 088464A1. In this method, ethylene or a mixture of ethylene and C3-C10 α-olefins is polymerized in an organic solvent using a Ziegler catalyst or a single-site catalyst to form an initial polyethylene solution. The initial polyethylene solution is then reacted with a free radical initiator to produce a modified polyethylene. The modified polymer has enhanced melt elasticity and an increased long chain branching index and is substantially free of gel.
[0005] Examples of compositions suitable for the use are disclosed in WO2018095700, WO2018095701 and WO2018095702.
[0006] Due to the proper selection of their molecular structure and rheological behavior, the compositions achieve exceptionally high environmental stress crack resistance (ESCR) over a wide density range, and the final article has an extremely smooth surface and reduced gel content.
[0007] At high density levels, ESCR decreases but remains satisfactory.
[0008] However, a key aspect of blow molding that may need to be optimized is the expansion behavior of the polymer composition.
[0009] In fact, the overall quality level and quality consistency of blow molded products depend to a large extent on expansion.
[0010] For example, in extrusion blow molding, parison expansion is very important.
[0011] There are two components to parison expansion: weight expansion and diameter expansion.
[0012] Weight expansion can occur in the short time between the mold opening and the parison dropping. The parison may actually decrease in length while its walls thicken and become heavier.
[0013] Excessive weight expansion should be avoided, especially for producing blow molded parts with thin, constant wall thickness and low weight. Die adjustment can be critical.
[0014] If the weight swell of the resin used is too high, attempts are often made to reduce the weight by reducing the mold gap.
[0015] However, reducing the die gap may produce a very thin parison that collapses and folds quickly.
[0016] In addition, a narrow die gap is extremely sensitive to impurities. A narrow die gap also results in high shear, which can cause high diameter expansion in the parison. The final bottle may be intact but have thick flash around it. Wrinkles can also be a problem.
[0017] Therefore, in terms of commonly used industry standards, weight expansion should be kept within practical limits.
[0018] Due to the diameter expansion, the parison expands outward from the die; in other words, the diameter of the parison becomes much larger than the diameter of the die.
[0019] Diameter expansion is particularly important for blow molded articles (especially bottles) that include a handle portion, and are therefore often referred to as "handle articles".
[0020] In this case, the diameter expansion may be expressed as the distance (length), for example in centimeters, that the flash extends from the neck of the handle article (including the protruding flash) to the handle region and possibly beyond the handle region.
[0021] In fact, resin that expands too little in diameter may cause the lower handle to reticulate or even burst in severe cases.
[0022] In this case, the parison is clamped in two places by the inner handle cutouts.
[0023] During blow molding, these regions merge to form thick regions known as the web.
[0024] As mentioned previously, resins with too high a diameter expansion will produce an undesirable amount of flash and thus cause trimming problems.
[0025] In summary, it is very important to provide polyethylene compositions having an inherently good and consistent expansion behavior.
[0026] It is well known that the expansion behavior of polyethylene compositions can be modified by treatment with free radical initiators, in particular peroxides, as disclosed, for example, in US Pat. No. 4,603,173 and US Pat. No. 5,486,575.
[0027] Furthermore, high-density, high-polydispersity polyethylenes with improved properties and processes for their production are known in the art, for example in WO 2018 / 147968 A1.
[0028] It has now been found that by appropriate setting of the molecular structure and selected rheological properties of the polyethylene composition, for example by postpolymerization treatment with free radical initiators, a particularly advantageous balance of parison expansion and mechanical properties can be achieved with a reduced gel content. Summary of the invention
[0029] Therefore, the present disclosure provides a polyethylene composition having the following characteristics:
[0030] 1) a MIF / MIE ratio greater than 125, preferably equal to or greater than 130, more preferably equal to or greater than 132, in particular from greater than 125 to 180 or from 130 to 180 or from 132 to 180, wherein MIF is the melt flow index at 190°C and a load of 21.60 kg, and MIE is the melt flow index at 190°C and a load of 2.16 kg, both measured according to ISO 1133-12012-03;
[0031] 2) MIF is from 20 to 40 g / 10 min, preferably from 25 to 35 g / 10 min, more preferably from 25 to 34 g / 10 min;
[0032] 3) Density from 0.948 to 0.960 g / cm 3 , especially from 0.950 to 0.958 g / cm 3 , measured at 23°C according to ISO 1183-1:2012;
[0033] 4) ER value is from 5 to 10, preferably from 5.2 to 9;
[0034] The ER is calculated according to the following formula:
[0035] ER=(1.781*10 -3 )*G'
[0036] G" value = 5,000 dyn / cm 2 ;
[0037] in:
[0038] G' = storage modulus;
[0039] G” = loss modulus;
[0040] Both G' and G" were measured at a temperature of 190°C using dynamic oscillatory shear in a plate-plate rotational rheometer.
[0041] The polyethylene composition can be easily processed in conventional blow-molding equipment since it meets the industrial requirements with respect to weight expansion and diameter expansion. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] These and other features, aspects and advantages of the present disclosure will become better understood with reference to the following description and appended claims and accompanying drawings, in which:
[0043] Figure 1 is an illustrative embodiment of a simplified process flow diagram of two series-connected gas phase reactors suitable for producing various embodiments of the polyethylene compositions disclosed herein according to various embodiments of the ethylene polymerization processes disclosed herein.
[0044] Figure 2 Depicted is a test bottle for weight and diameter expansion testing. It is approximately 28 cm high (excluding top and bottom flash) and approximately 14 cm wide
[0045] It should be understood that the various embodiments are not limited to the arrangements and instrumentality shown in the drawings. DETAILED DESCRIPTION
[0046] The expression "polyethylene composition" is intended to cover as an alternative single ethylene polymer and ethylene polymer compositions, in particular compositions of two or more ethylene polymer components, preferably of different molecular weights, such compositions also known in the relevant art as "bimodal" or "multimodal" polymers.
[0047] Typically, the present polyethylene composition consists of or comprises one or more ethylene copolymers.
[0048] All features defined herein including previously defined features 1) to 4) relate to the ethylene polymer or ethylene polymer composition. Addition of further components, such as additives commonly employed in the art, may modify one or more of the features described.
[0049] The MIF / MIE ratio provides a rheological measure of the molecular weight distribution.
[0050] Another measure of molecular weight distribution is given by M w / M n Than provided, where M w is the weight average molecular weight, and M n is the number average molecular weight, measured by GPC (gel permeation chromatography), as explained in the examples.
[0051] The preferred M of the polyethylene composition w / M n The value ranges from 15 to 35, in particular from 20 to 35.
[0052] M w The values are preferably from 150,000 g / mol to 450,000 g / mol, in particular from 150,000 g / mol to 350,000 g / mol.
[0053] In addition, the present polyethylene composition preferably has at least one of the following additional features:
[0054] - a comonomer content equal to or less than 1.7% by weight, in particular from 0.1 to 1.7% by weight (FTIR), relative to the total weight of the composition;
[0055] - MIP is 0.3 g / 10 min or more, more preferably 0.5 g / 10 min or more, in particular from 0.3 to 4 g / 10 min, or from 0.5 to 4 g / 10 min, wherein MIP is the melt flow index at 190° C. and a load of 5 kg, determined according to ISO 1133-1 2012-03;
[0056] - (MIF / MIE) / ER ratio is between MIF / MIE and ER, equal to or less than 26, more preferably equal to or less than 25.5, in particular from 26 to 15, or from 25.5 to 15, or from 26 to 20, or from 25.5 to 20;
[0057] - long chain branching index LCBI equal to or greater than 0.55, more preferably equal to or greater than 0.60, in all cases the upper limit is preferably 0.95;
[0058] Wherein LCBI is the ratio of the measured mean square radius of gyration Rg measured by GPC-MALLS at a molecular weight of 1,000,000 g / mol to the mean square radius of gyration of a linear PE having the same molecular weight;
[0059] -η 0.02 Equal to or greater than 56,000 Pa.s, in particular from 56,000 to 80,000 Pa.s;
[0060] where η 0.02is the complex viscosity of the melt, measured in a parallel-plate (or so-called plate-plate) rheometer in dynamic oscillatory shear mode with an applied angular frequency of 0.02 rad / s at a temperature of 190 °C;
[0061] -(η 0.02 / 1000) / LCBI ratio in η 0.02 Divided by 1000 and between LCBI, from 85 to 150, preferably from 90 to 130;
[0062] - HMWcopo index from 0.5 to 5, in particular from 0.5 to 3.5;
[0063] Wherein the HMWcopo index is determined according to the following formula:
[0064] HMWcopo=(η 0.02 xt maxDSC ) / (10^5)
[0065] where t maxDSC It is the time (in minutes) required to reach the maximum value of the heat flow for crystallization (in mW) at a temperature of 124°C under static conditions (time to reach the maximum crystallization rate, equivalent to t1 / 2 the crystallization half-time), measured in isothermal mode in a differential scanning calorimeter DSC.
[0066] The comonomer or comonomers present in the ethylene copolymer are generally selected from olefins having the formula CH2=CHR, wherein R is a linear or branched alkyl radical having from 1 to 10 carbon atoms.
[0067] Specific examples are propylene, butene-1, pentene-1, 4-methylpentene-1, hexene-1, octene-1 and decene-1. A particularly preferred comonomer is hexene-1.
[0068] Preferably, the present polyethylene composition is obtained by using a Ziegler-Natta polymerisation catalyst in the polymerisation stage, details of which are provided below.
[0069] As mentioned before, the present polyethylene composition can be advantageously used for producing blow-molded articles, in particular articles having valuable properties such as bottles with handle portions.
[0070] In fact, preferably, it is characterized by an environmental stress cracking resistance (measured by FNCT 6MPa / 50C) equal to or higher than 40h, in particular from 40 to 100h.
[0071] The gel content of the polyethylene composition is preferably less than 10 gels / m 2 , more preferably less than 5 gels / m 2 , with a diameter greater than 450μm.
[0072] The total gel content is preferably less than 500 gels / m 2 , more preferably less than 400 gels / m 2 .
[0073] The expansion ratio of the present polyethylene composition is preferably equal to or higher than 160%, in particular from 160% to 200%.
[0074] Details of the test methods are given in the examples.
[0075] The blow molding process is generally carried out by first plasticizing the polyethylene composition in an extruder at a temperature ranging from 180 to 250° C. and then extruding it through a compression mold into a blow molding mold where it is cooled.
[0076] In a preferred embodiment, the present polyethylene composition having the characteristics defined above is obtained by contacting a free radical initiator with a precursor polyethylene composition (I) having a MIF / MIE ratio lower than 1) and preferably equal to or lower than 120, more preferably equal to or lower than 115, in particular from 90 to 120 or from 90 to 115. I ) ratio; 1) / 1 I ) is the ratio of the MIF / MIE 1 of the final polyethylene composition (after contact with the free radical initiator) to the MIF / MIE 1 of the precursor polyethylene composition (I) I ), equal to or greater than 1.05, preferably equal to or greater than 1.1, in particular from 1.05 or from 1.1 to 1.8, or from 1.05 or from 1.1 to 1.6.
[0077] Preferably, the ER 4) of the final polyethylene composition (after contact with the free radical initiator) is about the same as the ER 4 of the precursor polyethylene composition (I). I ) between 4) / 4 I ) ratio is from 1.1 to 2.5.
[0078] In particularly preferred embodiments, the precursor polyethylene composition (I) has the following additional features:
[0079] 2 I )MIF is from 30 to 50 g / 10 min, preferably from 35 to 45 g / 10 min;
[0080] 3 I ) density from 0.948 to 0.960 g / cm 3 , especially from 0.950 to 0.958 g / cm 3 ;
[0081] 4 I)ER value is from 2 to 5, preferably from 2 to 4.5.
[0082] Furthermore, the precursor polyethylene composition (I) may preferably have at least one of the following additional features:
[0083] - a comonomer content equal to or less than 1.7 wt.-%, in particular from 0.1 to 1.7 wt.-% (FTIR), relative to the total weight of the composition, the comonomer(s) being the same as reported above for the final polyethylene composition; in particular, the type and amount of the comonomer(s) being the same in the final polyethylene composition (after contact with the free radical initiator) and in its precursor polyethylene composition (I);
[0084] - MIP is 0.3 g / 10 min or more, more preferably 0.5 g / 10 min or more, in particular from 0.3 to 6 g / 10 min, or from 0.5 to 6 g / 10 min;
[0085] - (MIF / MIE) / ER ratio is between MIF / MIE and ER, greater than 26, more preferably equal to or greater than 27, in particular from greater than 26 to 40, or from 27 to 40, or from greater than 26 to 35, or from 27 to 35;
[0086] - long chain branching index LCBI equal to or greater than 0.50, more preferably equal to or greater than 0.55, most preferably equal to or greater than 0.60, in all cases, the upper limit is preferably 0.90;
[0087] -η 0.02 Below 56,000 Pa.s, in particular from 55,000 to 30,000 Pa.s;
[0088] -(η 0.02 / 1000) / LCBI ratio in η 0.02 Between divided by 1000 and LCBI, from 55 to 75, preferably from 55 to 70;
[0089] - HMWcopo index from 0.5 to 5, in particular from 0.5 to 3.5;
[0090] In a particularly preferred embodiment, the precursor polyethylene composition (I) comprises:
[0091] A) 30 to 70 wt%, preferably 40 to 60 wt% of an ethylene homopolymer or copolymer (the homopolymer is preferred), the ethylene homopolymer or copolymer having a carbonyl group equal to or greater than 0.960 g / cm 3 A density of 50 g / 10 min, and a melt flow index MIE of 40 g / 10 min or more, preferably 50 g / 10 min or more, at 190° C. and a load of 2.16 kg according to ISO 1133;
[0092] B) 30 to 70% by weight, preferably 40 to 60% by weight, of an ethylene copolymer having a lower MIE value than that of A), preferably a MIE value of less than 0.5 g / 10 min.
[0093] The above percentage amounts are given relative to the total weight of A)+B).
[0094] The specific MIE range of component A) is:
[0095] -40 to 150 g / 10 min; or
[0096] -50 to 150 g / 10 min; or
[0097] -40 to 100 g / 10 min; or
[0098] -50 to 100 g / 10 min.
[0099] It has been found that the precursor polyethylene composition (I) can be prepared by a gas phase polymerisation process in the presence of a Ziegler-Natta catalyst.
[0100] Ziegler-Natta catalysts include the reaction product of an organometallic compound of Group 1, 2 or 13 of the Periodic Table of Elements and a transition metal compound of Group 4 to 10 of the Periodic Table of Elements (using the new numbering system). In particular, the transition metal compound may be selected from compounds of Ti, V, Zr, Cr and Hf, and is preferably supported on MgCl2.
[0101] Preferred organometallic compounds are organo-Al compounds.
[0102] Thus, in a preferred embodiment, the precursor polyethylene composition (I) is obtainable by using a Ziegler-Natta polymerisation catalyst, preferably a Ziegler-Natta catalyst comprising the reaction product of:
[0103] A) a solid catalyst component comprising Ti, Mg, Cl and one or more internal electron donor compounds ED;
[0104] B) an organo-Al compound; and optionally
[0105] C) External electron donor compound ED ext .
[0106] In particular, the solid catalyst component A) may comprise one internal electron donor ED selected from aliphatic monocarboxylic acid esters (EAA) and another internal donor ED selected from cyclic ethers (CE) I , the amount of the other internal donor is such that the EAA / CE molar ratio is from 0.02 to less than 20.
[0107] Preferably, the molar ratio of EAA / CE ranges from 0.2 to 16, more preferably from 0.5 to 10.
[0108] The internal donor compound (EAA) is preferably selected from C1-C 10 , preferably C2-C 10 , preferably C2-C6 alkyl esters of aliphatic monocarboxylic acids with C2-C5 alkyl groups. Among them, ethyl acetate is particularly preferred.
[0109] (CE) The internal donor is preferably selected from cyclic ethers having 3 to 5 carbon atoms, among which tetrahydrofuran, tetrahydropyran and dioxane are most preferred, and tetrahydrofuran is particularly preferred.
[0110] (EAA + CE) / Ti molar ratio is preferably higher than 1.5, and more preferably ranges from 2.0 to 10, especially from 2.5 to 8.
[0111] Relative to the total weight of the solid catalyst component, the content of (EAA) generally ranges from 1 to 30% by weight, more preferably from 2 to 20% by weight. Relative to the total weight of the solid catalyst component, the content of (CE) generally ranges from 1 to 20% by weight, more preferably from 2 to 10% by weight.
[0112] Preferably, the Mg / Ti molar ratio ranges from 5 to 50, more preferably from 10 to 40.
[0113] As disclosed above, in addition to the donor compound, the catalyst component also contains Ti, Mg and chlorine. The Ti atoms preferably come from Ti compounds containing at least Ti-halogen bonds, and the Mg atoms preferably come from magnesium dichloride. Preferred titanium compounds are tetrahalides or compounds of the formula TiX n (OR 1 ) 4-n , where 0 < n < 3, X is a halogen, preferably chlorine, and R 1 is a C1-C 10 hydrocarbyl group. Titanium tetrachloride is the preferred titanium compound.
[0114] The catalyst components of the present disclosure can be prepared according to different methods.
[0115] A preferred method includes the following steps: (a) contacting an MgX2(R 2 OH) m adduct (where the R 2 group is a C1-C 20 hydrocarbyl group and X is a halogen) with a liquid medium containing a Ti compound having at least a Ti-Cl bond, the amount of the Ti compound being such that the Ti / Mg molar ratio is greater than 3, thereby forming a solid intermediate;
[0116] (b) contacting the solid intermediate product from (a) with internal donor compounds (EAA) and (CE) as defined above, and then washing the resulting product.
[0117] Preferred starting MgX2(R 2 OH) m Adducts are those in which R 2 The group is C1-C 10 Alkyl groups, X is chlorine and m is from 0.5 to 4, more preferably from 0.5 to 2. This type of adduct can usually be obtained by mixing alcohol and magnesium chloride in the presence of an inert hydrocarbon immiscible with the adduct, operating under stirring conditions at the melting temperature of the adduct (100 to 130° C.). The emulsion is then rapidly quenched, thereby solidifying the adduct in the form of spherical particles. Representative methods for preparing these spherical adducts are reported in, for example, USP 4,469,648, USP 4,399,054 and WO98 / 44009. Another useful method for spheroidization is the spray cooling method described in, for example, USP 5,100,849 and 4,829,034.
[0118] Of particular interest is MgCl2(EtOH) m Adducts wherein m is from 0.15 to 1.5 and the particle size ranges from 10 to 100 μm, obtained by subjecting an adduct having a higher alcohol content to a thermal dealcoholation process in a nitrogen stream at a temperature between 50° C. and 150° C. until the alcohol content is reduced to the above values. This type of process is described in EP 395083.
[0119] The dealcoholation can also be carried out chemically by contacting the adduct with a compound capable of reacting with the alcohol group.
[0120] In general, these dealcoholate adducts are also characterized by a porosity (measured by the mercury method) ranging from 0.15 to 2.5 cm due to pores with a radius of up to 1 μm. 3 / g, preferably from 0.25 to 1.5 cm 3 / g.
[0121] The reaction with the Ti compound can be carried out by suspending the adduct in TiCl4 (usually cold); the mixture is then heated to a temperature ranging from 80°C to 130°C and maintained at this temperature for 0.5 to 2 hours. The treatment with the titanium compound can be carried out once or more. Preferably, it is carried out twice. At the end of the process, the intermediate solid is recovered by separating the suspension via conventional methods (such as sedimentation and removal of liquid, filtration, centrifugation), and can be washed with a solvent. Although washing is usually carried out with an inert hydrocarbon liquid, more polar solvents (having, for example, a higher dielectric constant) such as halogenated hydrocarbons can also be used.
[0122] As described above, in step (b), the intermediate solid is contacted with an internal donor compound under conditions to immobilize an amount of the donor on the solid such that the EAA / CE molar ratio ranges from 0.02 to less than 20.
[0123] Although not strictly required, the contact is usually carried out in a liquid medium such as a liquid hydrocarbon. The temperature at which the contact occurs can vary depending on the nature of the reagent. It is generally included in the range of from -10°C to 150°C, and preferably from 0°C to 120°C. Obviously, even if the temperature falls within a generally suitable range, a temperature that causes decomposition or degradation of any particular reagent should be avoided. In addition, the treatment time may also vary depending on other conditions such as the nature, temperature, concentration, etc. of the reagent. As a general indication, the contact step can last from 10 minutes to 10 hours, more often from 0.5 to 5 hours. If necessary, in order to further increase the final donor content, this step can be repeated one or more times.
[0124] At the end of this step, the solid is recovered by separating the suspension via conventional methods (such as settling and removing the liquid, filtering and centrifuging), and may be washed with a solvent. Although washing is usually carried out with an inert hydrocarbon liquid, more polar solvents (having, for example, a higher dielectric constant) such as halogenated hydrocarbons or oxygenated hydrocarbons may also be used.
[0125] According to a specific embodiment, it is particularly preferred to carry out a further step (c) after step (b), namely to heat-treat the solid catalyst component from (b) at a temperature of from 70°C to 150°C.
[0126] In step (c) of the process, the solid product recovered from step (b) is heat treated at a temperature of from 70°C to 150°C, preferably from 80°C to 130°C, more preferably from 85°C to 100°C.
[0127] The heat treatment can be carried out in various ways. According to one of these ways, the solid from step (b) is suspended in an inert diluent (such as a hydrocarbon) and then heated while maintaining the system under stirring.
[0128] According to an alternative technique, the solid can be heated in a dry state by inserting it into a device having jacketed heated walls. Although agitation can be provided by a mechanical stirrer placed within the device, agitation is preferably provided by using a rotating device.
[0129] According to yet another different embodiment, the solid from (b) may be heated by subjecting it to a flow of hot inert gas, such as nitrogen, preferably by keeping the solid under fluidized conditions.
[0130] The heating time is not fixed, but can vary according to other conditions (such as the maximum temperature reached). It is usually from 0.1 to 10 hours, more specifically from 0.5 to 6 hours. Generally, higher temperatures allow shorter heating times, while lower temperatures may require longer reaction times.
[0131] In the described process, each step (b) to (c) can be carried out immediately after the previous step without isolating the solid product from the previous step. However, if desired, the solid product from one step can be separated and washed before carrying out the subsequent step.
[0132] According to a particular embodiment, a preferred improvement of the process consists in subjecting the solid from step (a) to a prepolymerization step (a2) before carrying out step (b).
[0133] The prepolymerization can be carried out with any olefin CH2=CHR, wherein R is H or C1-C 10 Hydrocarbyl groups. In particular, it is particularly preferred to prepolymerize ethylene or propylene or a mixture thereof with one or more α-olefins, the mixture containing up to 20 mol % of α-olefins, so that the amount of polymer formed is from about 0.1 g to about 1000 g per gram of solid intermediate, preferably from about 0.5 to about 500 g per gram of solid intermediate, more preferably from 0.5 to 50 g per gram of solid intermediate, and especially from 0.5 to 5 g per gram of solid intermediate. The prepolymerization step can be carried out in the liquid phase or the gas phase at a temperature from 0°C to 80°C, preferably from 5°C to 70°C. It is particularly preferred that the intermediate is prepolymerized with ethylene or propylene to produce an amount of polymer of 0.5 to 20 g per gram of intermediate. The prepolymerization is carried out using a suitable cocatalyst (such as an organoaluminum compound). When the solid intermediate is prepolymerized with propylene, it is particularly preferred to carry out the prepolymerization in the presence of one or more external donors, which are preferably selected from the general formula R a 4 R b 5 Si(OR 6 ) c A silicon compound wherein a and b are integers from 0 to 2, c is an integer from 1 to 3, and the sum of (a+b+c) is 4; R 4 , R 5 and R 6 is an alkyl, cycloalkyl or aryl group having 1 to 18 carbon atoms, optionally containing heteroatoms. Particularly preferred are silicon compounds wherein a is 1, b is 1, c is 2, R 4 and R 5 At least one of is selected from a branched alkyl, cycloalkyl or aryl group having 3 to 10 carbon atoms, optionally containing a heteroatom, and R 6 It is C1-C 10Alkyl groups, in particular methyl. Examples of preferred silicon compounds of this type are methylcyclohexyldimethoxysilane (C donor), diphenyldimethoxysilane, methyl-tert-butyldimethoxysilane, dicyclopentyldimethoxysilane (D donor) and diisopropyldimethoxysilane.
[0134] All the above processes are suitable for preparing particles of the solid catalyst component having a substantially spherical morphology and an average diameter comprised between 5 and 150 μm, preferably from 10 to 100 μm. As particles having a substantially spherical morphology are meant particles wherein the ratio between the larger axis and the smaller axis is equal to or lower than 1.5, and preferably lower than 1.3.
[0135] Typically, the solid catalyst component obtained according to the above process exhibits a surface area (by the BET method) typically between 10 and 200 m 2 / g, and preferably between 20 and 80 m 2 / g, and the total porosity (by BET method) is higher than 0.15 cm 3 / g, preferably between 0.2 and 0.6 cm 3 / g. From radius to The pore-induced porosity (mercury method) typically ranges from 0.25 to 1 cm 3 / g, preferably from 0.35 to 0.8 cm 3 / g.
[0136] As previously mentioned, the catalyst components of the present disclosure form polymerization catalysts by reacting with Al-alkyl compounds. In particular, Al-trialkyl compounds, such as Al-trimethyl, Al-triethyl, Al-tri-n-butyl, Al-tri-isobutyl are preferred. The Al / Ti ratio is higher than 1 and is generally comprised between 5 and 800.
[0137] In addition, alkylaluminum halides, in particular alkylaluminum chlorides, such as diethylaluminum chloride (DEAC), diisobutylaluminum chloride, aluminum trichloride and dimethylaluminum chloride (DMAC) can also be used. It is also possible and in some cases preferred to use mixtures of trialkylaluminum compounds with alkylaluminum halides. Among them, the mixtures TEAL / DEAC and TIBA / DEAC are particularly preferred.
[0138] Optionally, an external electron donor (ED) can be used during the polymerization ext The external electron donor compound may be the same as or different from the internal donor used in the solid catalyst component. Preferably, it is selected from the group consisting of ethers, esters, amines, ketones, nitriles, silanes and mixtures thereof. In particular, it may be advantageously selected from C2-C 20Aliphatic ethers, and particularly cyclic ethers having 3 to 5 carbon atoms such as tetrahydrofuran and dioxane are preferred.
[0139] In addition to the aluminum alkyl cocatalyst (B) and possibly an external electron donor (ED ext ) as component (C), a halogenated compound (D) can also be used as an activity enhancer. The compound is preferably a monohalogenated hydrocarbon or a dihalogenated hydrocarbon. In a preferred embodiment, it is selected from a monohalogenated hydrocarbon in which a halogen is connected to a secondary carbon atom. The halogen is preferably selected from chlorides and bromides.
[0140] Non-limiting exemplary compounds of (D) are propyl chloride, isopropyl chloride, butyl chloride, sec-butyl chloride, tert-butyl chloride, 2-chlorobutane, cyclopentyl chloride, cyclohexyl chloride, 1,2-dichloroethane, 1,6-dichlorohexane, propyl bromide, isopropyl bromide, butyl bromide, sec-butyl bromide, tert-butyl bromide, isobutyl bromide, isopentyl bromide and tert-amyl bromide. Among them, particularly preferred are isopropyl chloride, 2-chlorobutane, cyclopentyl chloride, cyclohexyl chloride, 1,4-dichlorobutane and 2-bromopropane.
[0141] According to another embodiment, the compound may be selected from the group consisting of halogenated alcohols, esters or ethers, such as 2,2,2-trichloroethanol, ethyl trichloroacetate, butyl perchlorocrotonate, 2-chloropropionate and 2-chloro-tetrahydrofuran.
[0142] The activity enhancer may be used in an amount such that the (B) / (D) molar ratio is higher than 3, preferably in the range of 5-50, more preferably in the range of 10-40.
[0143] The above components (A) to (D) can be fed to the reactor separately under polymerization conditions to utilize their activity. However, precontacting of the above components (optionally in the presence of a small amount of olefin) over a period ranging from 1 minute to 10 hours (preferably in the range of from 2 to 7 hours) constitutes a particularly advantageous embodiment. The precontact can be carried out in a liquid diluent at a temperature ranging from 0°C to 90°C, preferably in the range of 20°C to 70°C.
[0144] One or more alkyl aluminum compounds or mixtures thereof may be used for precontacting. If more than one alkyl aluminum compound is used in the precontacting, they may be used together or added sequentially to the precontacting tank. Even if precontacting is performed, it is not necessary to add the entire amount of the alkyl aluminum compound at this stage. A portion of the alkyl aluminum compound may be added in the precontacting, while the remainder may be fed to the polymerization reactor. In addition, when more than one alkyl aluminum compound is used, one or more may also be used in the precontacting process and the other alkyl aluminum compounds may be fed to the reactor.
[0145] In one of the preferred embodiments, the precontact is carried out by first contacting the catalyst components with a trialkylaluminum, such as tri-n-hexylaluminum (THA), then adding another alkylaluminum compound, preferably diethylaluminum chloride, to the mixture, and finally adding another trialkylaluminum, preferably triethylaluminum, as the third component to the precontact mixture. According to a variant of the process, the last trialkylaluminum is added to the polymerization reactor.
[0146] The total amount of the alkylaluminum compound used can vary within wide limits but is preferably in the range from 2 to 10 mol per mol of internal donor in the solid catalyst component.
[0147] It has been found that by using the above-mentioned polymerization catalysts, the precursor polyethylene composition (I) can be prepared in any mutual order in a process comprising the following steps:
[0148] a) polymerizing ethylene, optionally together with one or more comonomers, in a gas phase reactor in the presence of hydrogen;
[0149] b) copolymerizing ethylene with one or more comonomers in another gas phase reactor in the presence of an amount of hydrogen which is less than that of step a);
[0150] wherein in at least one of the gas phase reactors, growing polymer particles flow upwards under fast fluidization or transport conditions through a first polymerization zone (riser), leave the riser and enter a second polymerization zone (downcomer), through which they flow downwards under the effect of gravity, leave the downcomer and are reintroduced into the riser, thereby establishing a circulation of the polymer between the two polymerization zones.
[0151] In the first polymerization zone (riser), fast fluidization conditions are established by feeding a gas mixture comprising one or more olefins (ethylene and comonomers) at a speed higher than the conveying speed of the polymer particles. The speed of the gas mixture is preferably comprised between 0.5 and 15 m / s, more preferably between 0.8 and 5 m / s. The terms "conveying speed" and "fast fluidization conditions" are well known in the art; for their definition, see, for example, "D. Geldart, Gas Fluidisation Technology, pp. 155 et seq., J. Wiley & Sons Ltd., 1986".
[0152] In the second polymerization zone (downcomer), the polymer particles flow in a densified form under the effect of gravity, reaching high values of solid density (mass of polymer per reactor volume), which are close to the bulk density of the polymer.
[0153] In other words, the polymer flows vertically downward through the downcomer in plug flow (fill flow mode) such that only small amounts of gas are entrained between the polymer particles.
[0154] Such a process allows to obtain from step a) an ethylene polymer having a lower molecular weight than the ethylene copolymer obtained from step b).
[0155] Preferably, the copolymerization of ethylene to produce a relatively low molecular weight ethylene copolymer (step a) is carried out upstream of the copolymerization of ethylene to produce a relatively high molecular weight ethylene copolymer (step b). To this end, in step a), a gaseous mixture comprising ethylene, hydrogen, comonomers and an inert gas is fed to a first gas phase reactor, preferably a gas phase fluidized bed reactor. The polymerization is carried out in the presence of the aforementioned Ziegler-Natta catalyst.
[0156] The feed rate of hydrogen depends on the specific catalyst used, and is particularly suitable for obtaining in step a) an ethylene polymer having a melt flow index MIE of 40g / 10min or higher. In order to obtain the above MIE scope, in step a), based on the cumulative volume of the gas present in the polymerization reactor, the hydrogen / ethylene molar ratio is indicated as from 1 to 4, and the amount of ethylene monomer is from 2 to 20 volume %, preferably from 5 to 15 volume %. The remainder of the feed mixture is represented by an inert gas and one or more comonomers (if any). The necessary inert gas for dissipating the heat generated by the polyreaction is conveniently selected from nitrogen or saturated hydrocarbons, most preferably propane.
[0157] The operating temperature in the reactor of step a) is selected between 50 and 120° C., preferably between 65 and 100° C., while the operating pressure is between 0.5 and 10 MPa, preferably between 2.0 and 3.5 MPa.
[0158] In a preferred embodiment the ethylene polymer obtained in step a) represents 30 to 70 wt.-% of the total ethylene polymer produced in the whole process, ie in the first and second serially connected reactors.
[0159] The ethylene polymer and entrained gas from step a) are then passed through a solid / gas separation step to prevent the gaseous mixture from the first polymerization reactor from entering the reactor of step b) (second gas phase polymerization reactor). The gaseous mixture can be recycled back to the first polymerization reactor while the separated ethylene polymer is fed to the reactor of step b). A suitable point for feeding the polymer into the second reactor is on the connection between the downcomer and the riser, where the solids concentration is particularly low, so that the flow conditions are not negatively affected.
[0160] The operating temperature in step b) is in the range of 65 to 95° C. and the pressure is in the range of 1.5 to 4.0 MPa. The second gas phase reactor is intended to produce a relatively high molecular weight ethylene copolymer by copolymerizing ethylene with one or more comonomers. In addition, in order to broaden the molecular weight distribution of the final ethylene polymer, the reactor of step b) can be conveniently operated by establishing different conditions of monomer and hydrogen concentration in the riser and downcomer.
[0161] For this reason, in step b), it is possible to partially or completely prevent the entrained polymer particles and the gas mixture from the riser from entering the downcomer, thereby obtaining two different gas composition zones. This can be achieved by feeding the gas and / or liquid mixture into the downcomer by being placed at a suitable point of the downcomer, preferably in the pipeline feed at its upper part. The gas and / or liquid mixture should have a suitable composition different from the gas mixture present in the riser. The flow of the gas and / or liquid mixture can be adjusted so that an upward gas flow countercurrent to the flow of the polymer particles is generated, particularly at its top, acting as a separator of the gas mixture entrained in the polymer particles from the riser. In particular, it is advantageous that the feed has a mixture of low hydrogen content to produce a polymer fraction of higher molecular weight in the downcomer. One or more comonomers can be optionally fed to the downcomer of step b) together with ethylene, propane or other inert gases.
[0162] The hydrogen / ethylene molar ratio in the downcomer of step b) is comprised between 0.005 and 0.2, the ethylene concentration is comprised between 0.5 and 15 volume %, preferably between 0.5 and 10 volume %, and the comonomer concentration is comprised between 0.05 and 1.5 volume %, based on the total volume of gas present in said downcomer. The remainder is propane or similar inert gas. Due to the presence of very low molar concentrations of hydrogen in the downcomer, by implementing the present process, relatively high amounts of comonomer can be bonded to the high molecular weight polyethylene fraction.
[0163] The polymer particles from the downcomer are reintroduced into the riser of step b).
[0164] Since the polymer particles remain reacting and no more comonomer is fed into the riser, the comonomer concentration falls to a range of 0.05 to 1.2% by volume, based on the total volume of gas present in the riser. In practice, the comonomer content is controlled to obtain the desired density of the final polyethylene. In the riser of step b), the hydrogen / ethylene molar ratio is in the range of 0.01 to 0.5, and the ethylene concentration is comprised between 5 and 20% by volume, based on the total volume of gas present in the riser. The remainder is propane or other inert gases.
[0165] Further details on the above mentioned polymerization process are provided in WO2005019280.
[0166] The precursor polyethylene composition (I) thus obtained is then contacted with a free radical initiator.
[0167] "Contacting" means that the precursor polyethylene composition (I) and the free radical initiator are mixed together and react with each other.
[0168] The free radical initiator is preferably selected from organic peroxides.
[0169] Particularly useful organic peroxides are organic monoperoxides and / or organic diperoxides. These organic monoperoxides and diperoxides can have a half-life of 1 hour at the following temperature: from about 125°C to about 145°C in the range, or from about 130°C to about 140°C in the range, or from about 132°C to about 136°C in the range. Other alternatives are included in organic peroxides with a half-life of 0.1 hour at the following temperature: from about 145°C to 165°C in the range, or from about 150°C to about 160°C in the range, or from about 154°C to 158°C in the range. Organic peroxides can have a molecular weight in the range of from about 175g / mol to about 375g / mol, or from about 200g / mol to about 350g / mol. If desired, a mixture of two or more peroxides can be used.
[0170] Suitable organic peroxides include, but are not limited to, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 3,6,9-triethyl-3,6,9-trimethyl-1,2,4,5,7,8-hexanone, representative 3,6,9-trimethyl-3,6,9-tri(alkyl)-1,2,4,5,7,8-hexanone wherein the alkyl radical is propyl or ethyl, tert-butyl peroxyneodecanoate, tert-amyl peroxypivalate, 1,3-bis(tert-butylperoxyisopropyl)benzene, and the like.
[0171] Preferably, the organic peroxide is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 3,6,9-triethyl-3,6,9-trimethyl-1,2,4,5,7,8-hexanone or a representative 3,6,9-trimethyl-3,6,9-tri(alkyl)-1,2,4,5,7,8-hexanone wherein the alkyl radical is propyl or ethyl.
[0172] In a preferred embodiment of the present disclosure, the organic peroxide is employed in the form of a polyolefin mixture, which is preferably prepared by adding the organic peroxide in pure form or as a solution of the organic peroxide in a diluent such as a hydrocarbon to a polyolefin powder. In the polyolefin mixture, the preferred polyolefin mixture has an organic peroxide content in the range of from 0.5 to 25 wt%, preferably from 1 to 20 wt%, and more preferably from 2 to 10 wt%.
[0173] Preferably, the amount of one or more organic peroxides added is from 10 to 100 ppm by weight, more preferably from 25 to 90 ppm by weight, in particular from 25 to 80 ppm by weight, corresponding to the content of initiator in the precursor polyethylene composition (I).
[0174] Contacting with the free radical initiator may be carried out by any means and under conditions known in the art to be effective for free radical initiation of reactions in olefin polymers.
[0175] As is well known, such reactions can be carried out in conventional equipment usually used for processing polymers in the molten state.
[0176] In particular, the polyethylene composition of the present disclosure can be prepared by contacting the precursor polyethylene composition (I) with a free radical initiator in an extruder device. Suitable extruder devices are extruders or continuous mixers. These extruders or mixers can be single-stage or two-stage machines that melt and homogenize the polyethylene composition. Examples of extruders are pin extruders, planetary extruders or co-rotating disc processing machines. Other possibilities are the combination of a mixer with a discharge screw and / or a gear pump. Preferred extruders are screw extruders, and in particular are extruders configured as twin-screw machines. Twin-screw extruders and continuous mixers with discharge elements are particularly preferred, and in particular continuous mixers with counter-rotating twin rotors, or the extruder device comprises at least one co-rotating twin-screw extruder. Machines of this type are conventional in the plastics industry and are manufactured, for example, by Coperion GmbH, Stuttgart, Germany; KraussMaffei Berstorff GmbH, Hannover, Germany; The Japan Steel Works LTD., Tokyo, Japan; Farrel Corporation, Ansonia, USA; or Kobe Steel, Ltd., Kobe, Japan. Suitable extruder devices are usually also equipped with a unit for pelletizing the melt, such as an underwater pelletizer.
[0177] The contact and reaction temperature is preferably in the range of from 180° C. to 350° C., in particular from 180° C. to 300° C., and is generally equal to or higher than the decomposition temperature of the free radical initiator.
[0178] For most operations, especially large-scale operations, the contact and reaction time is preferably several times the half-life of the initiator. This provides a substantially complete reaction and minimizes the possibility of undesirable initiator residues in the polyethylene composition. Although small amounts of undecomposed initiator will not cause harm, the presence of large amounts of unreacted initiator may lead to gel formation and other undesirable effects during subsequent processing of the polyethylene composition.
[0179] Furthermore, one or more additives may be fed to the polyethylene composition.
[0180] The feeding of these additives may take place before, during or after the contacting of the precursor polyethylene composition (I) with the free radical initiator.
[0181] Such additives are common in the art. The additive of the suitable type for preparing the polyethylene composition is, for example, an antioxidant, a melt stabilizer, a light stabilizer, an acid scavenger, a lubricant, a processing aid, an antiblocking agent, a smoothing agent, an antistatic agent, an antifogging agent, a pigment or a dye, a nucleating agent, a flame retardant or a filler. Several additives are usually added. Various additives can be different types of additives. However, several additives representing a type can also be added to the polyethylene composition. All these types of additives are usually commercially available, and are described in, for example, Hans Zweifel's " Plastics Additives Handbook (Plastics Additives Handbook) " (5th edition, Munich (Munich), 2001).
[0182] Example
[0183] Various embodiments, compositions and methods provided herein are disclosed in the following examples. These examples are merely illustrative and are not intended to limit the scope of the appended claims in any way.
[0184] The following analytical methods were used to characterize the polymer compositions.
[0185] Melt flow index
[0186] Determined according to ISO 1133-1 2012-03 at 190°C and specified load.
[0187] density
[0188] Measured at 23°C according to ISO 1183-1:2012.
[0189] Molecular weight distribution determination
[0190] The average values Mw and Mn and the Mw / Mn derived therefrom were determined by high temperature gel permeation chromatography using the method described in ISO 16014-1, -2, -4 published in 2003. The details according to the ISO standard are as follows: solvent 1,2,4-trichlorobenzene (TCB), temperature of the apparatus and solution 135°C, and a PolymerChar (Valencia, Paterna 46980, Spain) IR-4 infrared detector that can be used with TCB as a concentration detector. A WATERS Alliance 2000 equipped with the following precolumn SHODEX UT-G and separation columns SHODEX UT 806M (3x) and SHODEX UT 807 (Showa Denko Europe GmbH, Konrad-Zuse-Platz 4, 81829 Muenchen, Germany) connected in series was used.
[0191] The solvent was vacuum distilled under nitrogen and stabilized with 0.025 wt % 2,6-di-tert-butyl-4-methylphenol. The flow rate used was 1 ml / min, the injection volume was 500 μl, and the polymer concentration was in the range of 0.01%<concentration<0.05% w / w. Molecular weight calibration was established by using monodisperse polystyrene (PS) standards from polymer laboratories (now Agilent Technologies, Herrenberger Str. 130, 71034 Boeblingen, Germany)) and additionally hexadecane in the range of 580 g / mol to 11600000 g / mol.
[0192] The calibration curve was then adapted to polyethylene (PE) by the universal calibration method (Benoit H., Rempp P. and Grubisic Z., & in J. Polymer Sci., Phys. Eds., 5, 753 (1967)). The Mark-Houwing parameters used here for PS are: k PS =0.000121dl / g, α PS =0.706, and for PE, k PE =0.000406dl / g, α PE= 0.725, valid in TCB at 135° C. Data recording, calibration and calculation were performed using NTGPC_Control_V6.02.03 and NTGPC_V6.4.24 (hs GmbH, Hauptstraβe 36, D-55437 Ober-Hilbersheim, Germany), respectively.
[0193] Long Chain Branching Index (LCBI)
[0194] The LCB index corresponds to 10 6 The branching factor g' is measured as a molecular weight of g / mol. The branching factor g' is measured by gel permeation chromatography (GPC) together with multi-angle laser light scattering (MALLS), which allows the determination of long chain branches at high Mw. The radius of gyration of each fraction eluted from GPC (as described above, but with a flow rate of 0.6 ml / min and a column filled with 30 μm particles) is measured by analyzing light scattering at different angles with MALLS (detector Wyatt Dawn EOS, Wyatt Technology, Santa Barbara, Calif.). A laser source of 120 mW with a wavelength of 658 nm is used. The specific refractive index is taken as 0.104 ml / g. Data evaluation is performed using Wyatt ASTRA 4.7.3 and CORONA 1.4 software. The LCB index is determined as described below.
[0195] The parameter g' is the ratio of the measured mean square radius of gyration to the mean square radius of gyration of a linear polymer with the same molecular weight. Linear molecules show a g' of 1, while values less than 1 indicate the presence of LCB. The value of g' as a function of the molecular weight M is calculated by the following equation:
[0196] g'(M)= <Rg 2 > 样品,M / <Rg 2 > 线性参考,M
[0197] in <Rg 2 >, M is the root mean square radius of gyration of the fraction with molecular weight M.
[0198] The radius of gyration of each fraction eluted from the GPC (as above, but with a flow rate of 0.6 ml / min and a column packed with 30 μm particles) was measured by analyzing light scattering at different angles. Thus, from this MALLS setup the molecular weight M and <Rg 2 > 样品,M and defined in the measurement M = 10 6 g' in g / mol. <Rg 2 > 线性参考,MIt was calculated from the established relationship between the radius of gyration and molecular weight of linear polymers in solution (Zimm and Stockmayer WH 1949) and confirmed by measuring a linear PE reference using the same equipment and methods as described.
[0199] The same protocol is described in the following papers.
[0200] Zimm BH, Stockmayer WH (1949) The dimensions of chain molecules containing branches and rings. J ChemPhys 17
[0201] Rubinstein M., Colby RH. (2003). Polymer Physics. Oxford University Press.
[0202] Complex shear viscosity η 0.02 (eta(0.02)) and ER
[0203] It was measured at an angular frequency of 0.02 rad / s and 190° C. as follows.
[0204] The sample is melt pressed at 200°C and 200 bar for 4 minutes into a 1 mm thick plate. A disc specimen with a diameter of 25 mm is punched out and inserted into a rheometer preheated at 190°C. Any commercially available rotational rheometer can be used for the measurement. An Anton Paar MCR 300 with a plate-plate geometry is used here. At T = 190°C, a so-called frequency sweep is carried out at a constant strain amplitude of 5% (after annealing the sample for 4 minutes at the measuring temperature), and the stress response of the material in the range of excitation frequency ω from 628 to 0.02 rad / s is measured and analyzed. Standardized basic software is used to calculate the rheological properties, namely the storage modulus G', the loss modulus G", the phase lag δ (= inverse tangent (G" / G')) and the complex viscosity η*, as a function of the applied frequency, i.e. η*(ω) = [G'(ω) 2 +G”(ω) 2 ] 1 / 2 / ω. The latter has a value of η at an applied frequency ω of 0.02rad / s 0.02 .
[0205] ER is determined by the method of R. Shroff and H. Mavridis, "New Measures of Polydispersity from Rheological Data on Polymer Melts," J. Applied Polymer Science, 57 (1995) 1605 (see also U.S. Pat. No. 5,534,472, col. 10, lines 20-30). Calculated from:
[0206] ER=(1.781*10 -3 )*G'
[0207] G" value = 5,000 dyn / cm 2 , where G' is defined as the storage modulus; and G" is defined as the loss modulus.
[0208] The ER value is defined as the polydispersity at the high end, and methods proposed in the literature for extracting polydispersity measurements from rheological data are reviewed. The requirements for valid polydispersity measurements are identified. The ER measurement is specifically used to quantify the high MW (or long term) end of polydispersity, especially when the ER value does not contain contributions from the low MW end.
[0209] As will be appreciated by those skilled in the art, when the minimum G" value is greater than 5,000 dyn / cm 2 When the rheometer is used, the determination of ER involves extrapolation. The calculated ER value will then depend on the nonlinearity in log G' versus log G". The temperature, plate diameter, and frequency range are selected so that the lowest G" value is close to or less than 5,000 dynes / cm within the resolution of the rheometer. 2 .
[0210] HMWcopo Index
[0211] To quantify the crystallization and processability potential of a polymer, the HMWcopo (high molecular weight copolymer) index is used, which is defined by the following formula:
[0212] HMWcopo=(η 0.02 xt maxDSC ) / (10^5)
[0213] It decreases as the polymer becomes easier to process (low melt viscosity) and more likely to crystallize rapidly. It is also descriptive and quantitative of the amount of high molecular weight fraction, and is similar to the complex shear viscosity of the melt at a frequency of 0.02 rad / s, measured as described above. 0.02 and the amount of comonomer incorporated to delay crystallization (as determined by the maximum heat flow time tmaxDSC quantified) related.
[0214] The t was measured under isothermal conditions at a constant temperature of 124 °C using a differential scanning calorimeter TA Instruments Q2000. maxDSC 5 to 6 mg of sample were weighed and placed in an aluminum DSC pan. The sample was heated to 200°C at 20 K / min and cooled to the test temperature also at 20 K / min in order to eliminate the thermal history. The isothermal test was started immediately afterwards and the time until crystallization occurred was recorded. The time interval t until the maximum (peak) of the crystallization heat flow was determined using the supplier's software (TA Instruments). maxDSC The measurement was repeated 3x and the average value (in minutes) was then calculated. If no crystallization was observed for more than 120 minutes under these conditions, t maxDSC The value at = 120 min was used for further calculations of the HMWcopo index.
[0215] The melt viscosity η 0.02 Multiply the value by t maxDSC The values were normalized by a factor of 100000 (10^5).
[0216] Expansion ratio
[0217] Using a capillary rheometer The expansion ratio of the investigated polymers was measured at T = 190 ° C by Rheotester 2000 and Rheograph 25, the capillary rheometer was equipped with a commercial 30 / 2 / 2 / 20 die (total length 30 mm, effective length = 2 mm, diameter = 2 mm, L / D = 2 / 2 and 20° angle of incidence) and an optical device for measuring the thickness of the extruded strand (from The sample was melted in a capillary tube at 190°C for 6 min and heated to a temperature corresponding to 1440 s -1 The piston speed at the die is the shear rate obtained by extrusion.
[0218] When the piston reaches a position of 96 mm from the die inlet, the extrudate is cut at a distance of 150 mm from the die outlet (by The extrudate diameter was measured as a function of time using a laser diode at 78 mm from the die exit. The maximum value corresponds to D 挤出物 The swelling ratio was determined by the following calculation:
[0219] SR=(D 挤出物 -D 压模 )100% / D 压模
[0220] Where D 压模is the corresponding diameter at the die exit measured with a laser diode.
[0221] Environmental stress cracking resistance according to the full notch creep test (FNCT)
[0222] The environmental stress cracking resistance of the polymer samples was determined in accordance with the international standard ISO 16770 (FNCT) in aqueous surfactant solutions. Compression-molded 10 mm thick sheets were prepared from the polymer samples. Rods with a square cross section (10×10×100 mm) were notched on four sides perpendicular to the stress direction using razor blades. The notching device described by M. Fleissner in Kunststoffe 77 (1987), page 45, was used for a sharp incision with a depth of 1.6 mm.
[0223] The applied load is calculated from the tensile force divided by the initial ligament area. The ligament area is the residual area = the total cross-sectional area of the specimen minus the cut area. For FNCT specimens: 10 x 10 mm 2 -4 times the trapezoidal cut area = 46.24mm 2 (Failure process / remaining cross section for crack extension). The test specimens were loaded with a constant load of 6 MPa at 50°C using the standard conditions recommended by ISO 16770 in a 2% (by weight) aqueous solution of the nonionic surfactant ARKOPAL N100. The time at which the test specimens broke was detected.
[0224] Weight expansion and diameter expansion (Uniloy test)
[0225] The weight and diameter expansion measurements were made simulating industrial process conditions using a Uniloy reciprocating blow molder model 5630 equipped with a 1 gallon center fill bottle mold and a parison drop time of approximately 1.1 seconds.
[0226] Weight swell is determined by adjusting the bottle weight to the required amount of 90 g using the reference resin Petrothene LR732002 and then comparing it to the weight of a bottle of the resin being checked produced under the same machine parameters.
[0227] Test bottle depicted in Figure 2 .
[0228] Therefore, the weight expansion is given by:
[0229] W B -90
[0230] Where W B is the weight of the test bottle in grams.
[0231] The diameter expansion is determined by measuring the flash on the bottle through the graduated markings, from the top (including the protruding top flash) down to and along the handle of the bottle at the same bottle weight as the reference resin (i.e., 90 g). The mold is adjusted relative to the parison so that the edge of the reference resin top flash falls on the 9 cm mark on the handle.
[0232] The machine parameters are:
[0233] Motor load / ampere. - Approximately 40 amps;
[0234] Screw speed - about 370 rpm (adjusted to adjust the parison tail length);
[0235] Hydraulic oil temperature -27 to 32°C (80-90°F);
[0236] Mold cooling temperature - inlet 4°C (39°F), outlet 8°C (47°F);
[0237] Injection pressure - 7MPa (1050psi);
[0238] Die pressure - 14 MPa (2000 psi);
[0239] Parison drop time - about 1.1 seconds;
[0240] Total cycle time - about 15.30 seconds;
[0241] Heating zone:
[0242] Feed - 330°F;
[0243] Transition - 177°C (350°F);
[0244] Metering 1-190°C (375°F);
[0245] Metering 2-190°C (375°F);
[0246] Adapter - 190°C (375°F);
[0247] Compression molding - 190°C (375°F);
[0248] Timer:
[0249] Pre-blow delay - 0.0 seconds;
[0250] Mold closing pause - 0.0 seconds;
[0251] Feed delay - 0.0 seconds;
[0252] Blow delay - 0.45 seconds;
[0253] Blowing time - 10.0 seconds;
[0254] Exhaust time - 2.0 seconds;
[0255] Injection delay - 0.0 seconds.
[0256] The reference resin Petrothene LR732002 is an ethylene polymer produced with a Cr catalyst having a FNCT 6MPa / 50°C of about 0.4 hours (measured as described above).
[0257] Other features of Petrothene LR732002 include:
[0258]
[0259] In these examples, diameter expansion was considered satisfactory when it fell within the range of 8 to 10 cm.
[0260] Cast film measurement
[0261] The film measurements of the gels were carried out on an OCS extruder model ME 202008-V3 with a screw diameter of 20 mm and a screw length of 25D and a slot die width of 150 mm. The casting line was equipped with a cooling roll and a winder (model OCS CR-9). The optical equipment consisted of an OSC film surface analyzer camera, model FTA-100 (flash camera system) with a resolution of 26 μm×26 μm. After first purging the resin for 1 hour to stabilize the extrusion conditions, the inspection and value recording were carried out after 30 minutes. The resin was extruded at 220°C with a take-off speed of ca. 2.7 m / min to produce a film with a thickness of 50 μm. The cooling roll temperature was 70°C.
[0262] The inspection with the surface analyzer camera provided the total content of gels and the content of gels with a diameter above 450 μm, as reported in Table 1.
[0263] Comonomer content
[0264] The comonomer content was determined by IR using a FT-IR spectrometer Tensor 27 from Bruker calibrated with a stoichiometric model for the determination of butyl side chains in PE (with hexene as comonomer) according to ASTM D 6248 98. The results were compared with the estimated comonomer content derived from the mass balance of the polymerization process and found to be consistent.
[0265] - Process settings
[0266] The polymerization process is carried out under continuous conditions in a facility comprising two gas phase reactors connected in series as shown in the figure.
[0267] The polymerization catalyst was prepared as follows.
[0268] Preparation of spherical catalyst carrier
[0269] A magnesium chloride and alcohol adduct containing about 3 moles of alcohol was prepared as described in Example 2 of USP 4,399,054, but operating at 2000 RPM instead of 10000 RPM.
[0270] The adduct thus obtained is dealcoholated via heat treatment at a temperature ranging from 50° C. to 150° C. under a nitrogen stream until the amount of alcohol is 25% by weight.
[0271] Preparation of solid catalyst components
[0272] At 0°C, 1 L of TiCl4 was introduced into a 2L four-necked round-bottom flask purged with nitrogen. Then, at the same temperature, 70 g of the spherical MgCl2 / EtOH adduct containing 25 wt% of ethanol prepared as described above was added under stirring. The temperature was raised to 130°C in 3 hours and maintained for 60 minutes. Then, stirring was interrupted, the solid product was allowed to settle and the supernatant was siphoned off. Fresh TiCl4 was added to a total volume of 1 L and the treatment was repeated at 130°C for 60 minutes. After settling and siphoning, the solid residue was washed five times with hexane at 50°C and twice with hexane at 25°C, and vacuum dried at 30°C.
[0273] 812cc of hexane was introduced into a 2L four-mouth glass reactor equipped with a stirrer at 10°C, and 50g of the catalyst component prepared as described above was introduced at 10°C while stirring. Keeping the internal temperature constant, 15g of a hexane solution of tri-n-octylaluminum (TNOA) (about 80g / l) and a certain amount of cyclohexylmethyl-dimethoxysilane (CMMS) (such as a molar ratio of TNOA / CMMS of 50) were slowly introduced into the reactor, and the temperature was kept at 10°C. After stirring for 10 minutes, a total amount of 65g of propylene was introduced into the reactor at a constant rate over 6.5 hours at the same temperature. Then, the entire contents were filtered and washed three times with hexane (100g / l) at a temperature of 30°C. After drying, the obtained prepolymerized catalyst (A) was analyzed and found to contain 55% by weight of polypropylene, 2.0% by weight of Ti, 9.85% by weight of Mg and 0.31% by weight of Al.
[0274] About 100 g of the solid prepolymerized catalyst prepared as described above was charged into a glass reactor purged with nitrogen and slurried with 1.0 L of hexane at 50°C.
[0275] Then, ethyl acetate (EAA) and tetrahydrofuran (CE) were carefully added dropwise (60') in such amounts that the molar ratio between Mg / EAA was 4 and the molar ratio between Mg and CE was 4.
[0276] The slurry was kept under stirring for 1.5 hours, still having an internal temperature of 50°C. Then, stirring was interrupted, the solid product was allowed to settle and the supernatant was siphoned off. The solid was washed once under stirring, anhydrous heptane was added to a volume of 1 L at 50°C, then stirring was interrupted, the solid product was allowed to settle and the supernatant was siphoned off. The volume was then restored to 1 L with anhydrous heptane, the temperature was raised to 85°C and kept under stirring for 2 hours. Then, stirring was interrupted, the solid product was allowed to settle and the supernatant was siphoned off.
[0277] The solid was washed 3 times with anhydrous hexane at 25°C (3 times, 1000 mL each time), recovered, dried under vacuum and analyzed, and the EAA / CE molar ratio was found to be 0.93.
[0278] Example 1 - Reference
[0279] Polyethylene is produced in a cascade fluidized bed reactor and a multizone circulation reactor having two interconnected reaction zones as shown in the figure.
[0280] For the polymerization, 9.8 g / h of the solid catalyst prepared as described above are fed into a first stirred precontact vessel using 0.75 kg / h of liquid propane, to which a mixture of triisobutylaluminum (TIBA) and diethylaluminum chloride (DEAC) is also fed. The weight ratio between triisobutylaluminum and diethylaluminum chloride is 7:1. The ratio between alkylaluminum and solid catalyst is 5:1. The first precontact vessel is maintained at 50°C with an average residence time of 35 minutes. The catalyst suspension of the first precontact vessel is continuously transferred to a second stirred precontact vessel, which is operated with an average residence time of 35 minutes and is also maintained at 50°C. The catalyst suspension is then continuously transferred to a fluidized bed reactor (FBR) (1) via pipeline (2).
[0281] In a fluidized bed reactor (1), ethylene is polymerized in the presence of propane as an inert diluent using hydrogen as a molecular weight regulator. 47.5 kg / h of ethylene, 175 g / h of hydrogen and 11 kg / h of propane are fed to the fluidized bed reactor (1) via line (3). No comonomer is added. The polymerization is carried out at a temperature of 80° C. and a pressure of 3.0 MPa. The selected feed rate results in an ethylene concentration in the reactor of 10.9% by volume and a hydrogen / ethylene molar ratio in the reactor of 2.6.
[0282] The polyethylene obtained in the fluidized bed reactor (1) had an MIE of 76 g / 10 min and an MIE of 0.967 g / cm 3 density.
[0283] The polyethylene obtained in the fluidized bed reactor (1) is continuously transferred to a multi-zone circulation reactor (MZCR) which is operated at a pressure of 2.6 MPa and a temperature of 85°C (measured at the point where the gas leaves the reactor). The internal diameter of the riser (4) is 200 mm and the length is 19 m. The total length of the downcomer (5) is 18 m, the upper part is 5 m, wherein the internal diameter is 300 mm, and the lower part is 13 m, wherein the internal diameter is 150 mm. In order to broaden the molecular weight distribution of the final ethylene polymer, the second reactor is operated by establishing different conditions of monomer and hydrogen concentration in the riser (4) and the downcomer (5). This is achieved by feeding a 330 kg / h liquid stream (liquid spacer) into the upper part of the downcomer (5) via pipeline (7). The liquid stream of pipeline 19 comes from the condensation step in the condenser 6, the working conditions are 56°C and 2.6 MPa, wherein a part of the circulating stream is cooled and partially condensed. As shown, the pump is located downstream of the condenser 6 .
[0284] The monomers entering the downcomer are fed at three locations. In feed point 1 (8), 25 kg / h of liquid condensate (10), 9 kg / h of ethylene (9) and 1025 g / h of 1-hexene (9) are introduced. In feed point 2 (11), 15 kg / h of liquid condensate (13) and 4.5 kg / h of ethylene (12) are introduced. In feed point 3 (14), 15 kg / h of liquid condensate (16) and 4.5 kg / h of ethylene (15) are fed. Through pipeline 19, 5 kg / h of propane, 27.8 kg / h of ethylene and 34 g / h of hydrogen are fed to the recycle system.
[0285] The final polymer is discontinuously discharged via line 18.
[0286] The first reactor produces about 50 wt% (split wt%) of the total amount of the final polyethylene resin produced by the first and second reactors.
[0287] The final MIF of the obtained precursor polyethylene composition (I) was 39.6 g / 10 min. The obtained density was 0.954 g / cm 3 .
[0288] The amount of comonomer (hexene-1) was about 1.05 wt%.
[0289] A portion of the resulting polymer powder (polymerized, ie without additives) was finally extruded on a Kobe mixer LCM80, with the addition of the following additives:
[0290] -1000ppm calcium stearate;
[0291] -800ppm Irganox 1010; and
[0292] - 1600 ppm Irgafos 168 (all ppm are by weight).
[0293] Irganox It is 2,2-bis[3-[,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl)-1-oxopropoxy]methyl]-1,3-propylene-3,5-bis(1,1-dimethylethyl)-4-hydroxybenzene-propionate, supplied by BASF SE, Ludwigshafen, Germany.
[0294] Irgafos is tris(2,4-di-tert-butylphenyl)phosphite, sold by Ciba Geigy.
[0295] The polymer powder and the additives were introduced into the inlet of the mixer at a rate of 170 kg / h and a screw speed of 800 rpm. There was a throttle valve between the two mixing zones, which was adjusted to a position where the temperature before the throttle valve was 220° C. There was a gear pump after the second mixing zone, and its suction pressure was set to 0.1 MPa (1.0 bar).
[0296] Polymerization conditions and polymer data (after extrusion) are reported in Table 1.
[0297] Example 2 - Comparative
[0298] A portion of the polymer powder of Example 1 (after polymerization) was extruded together with 1000 ppm calcium stearate, 800 ppm Irganox 1010, 1600 ppm Irgafos 168 and 133 ppm Pergaprop 7.5PP (all ppm by weight).
[0299] Pergaprop PERGAN(R) is a 7.5 wt% mixture of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and polypropylene supplied by PERGAN GmbH, Bocholt, Germany.
[0300] The same extrusion equipment and conditions as in Example 1 were used.
[0301] The polymer data are reported in Table 1.
[0302] Example 3 - Comparative
[0303] A portion of the polymer powder of Example 1 (after polymerization) was extruded together with 1000 ppm calcium stearate, 800 ppm Irganox 1010, 1600 ppm Irgafos 168 and 267 ppm Pergaprop 7.5PP (all ppm by weight).
[0304] The same extrusion equipment and conditions as in Example 1 were used.
[0305] Example 4
[0306] A portion of the polymer powder of Example 1 (after polymerization) was extruded together with 1000 ppm calcium stearate, 800 ppm Irganox 1010, 1600 ppm Irgafos 168 and 400 ppm Pergaprop 7.5PP (all ppm by weight).
[0307] The same extrusion equipment and conditions as in Example 1 were used.
[0308] The polymer data are reported in Table 1.
[0309] Example 5
[0310] A portion of the polymer powder of Example 1 (after polymerization) was extruded together with 1000 ppm calcium stearate, 800 ppm Irganox 1010, 1600 ppm Irgafos 168 and 533 ppm Pergaprop 7.5PP (all ppm by weight).
[0311] The same extrusion equipment and conditions as in Example 1 were used.
[0312] The polymer data are reported in Table 1.
[0313] Example 6
[0314] A portion of the polymer powder of Example 1 (after polymerization) was extruded together with 1000 ppm calcium stearate, 800 ppm Irganox 1010, 1600 ppm Irgafos 168 and 800 ppm Pergaprop 7.5PP (all ppm by weight).
[0315] The same extrusion equipment and conditions as in Example 1 were used.
[0316] The polymer data are reported in Table 1.
[0317] Table 1
[0318]
[0319]
[0320] Note: C2H4 = ethylene; C6H 12 = Hexene; * 2% Arkopal N100 aqueous solution
Claims
1. A polyethylene composition, the polyethylene composition having the following characteristics: 1) a MIF / MIE ratio greater than 125, preferably equal to or greater than 130, more preferably equal to or greater than 132, in particular from greater than 125 to 180 or from 130 to 180 or from 132 to 180, wherein MIF is the melt flow index at 190°C and a load of 21.60 kg, and MIE is the melt flow index at 190°C and a load of 2.16 kg, both determined according to ISO 1133-1 2012-03; 2) MIF is from 20 to 40 g / 10 min, preferably from 25 to 35 g / 10 min, more preferably from 25 to 34 g / 10 min; 3) Density from 0.948 to 0.960 g / cm 3 , especially from 0.950 to 0.958 g / cm 3 , measured at 23°C according to ISO 1183-1:2012; 4) ER value is from 5 to 10, preferably from 5.2 to 9; The ER is calculated according to the following formula: IS=(1.781*10 -3 )*G' G" value = 5,000 dyn / cm 2 ; in: G' = storage modulus; G” = loss modulus; Both G' and G" were measured at a temperature of 190°C using dynamic oscillatory shear in a plate-plate rotational rheometer.
2. The polyethylene composition according to claim 1, obtained by contacting a free radical initiator with a precursor polyethylene composition (I) having a MIF / MIE ratio lower than 1) and preferably equal to or lower than 120, more preferably equal to or lower than 115, in particular from 90 to 120 or from 90 to 115. I ) ratio; 1) / 1 I ) is a ratio of the MIF / MIE 1 of the final polyethylene composition (after contact with the free radical initiator) to the MIF / MIE 1 of the precursor polyethylene composition (I). I ), equal to or greater than 1.05, preferably equal to or greater than 1.1, in particular from 1.05 or from 1.1 to 1.8, or from 1.05 or from 1.1 to 1.
6.
3. The polyethylene composition according to claim 2, wherein the precursor polyethylene composition (I) has the following additional features: 2 I )MIF is from 30 to 50 g / 10 min, preferably from 35 to 45 g / 10 min; 3 I ) density from 0.948 to 0.960 g / cm 3 , especially from 0.950 to 0.958 g / cm 3 ; 4 I )ER value is from 2 to 5, preferably from 2 to 4.
5.
4. The polyethylene composition according to claim 2, wherein the precursor polyethylene composition (I) comprises: A) 30 to 70 wt%, preferably 40 to 60 wt% of an ethylene homopolymer or copolymer (the homopolymer is preferred), the ethylene homopolymer or copolymer having a carbonyl group equal to or greater than 0.960 g / cm 3 A density of 50 g / 10 min, and a melt flow index MIE of 40 g / 10 min or more, preferably 50 g / 10 min or more, at 190° C. and a load of 2.16 kg according to ISO 1133; B) 30 to 70 wt. %, preferably 40 to 60 wt. %, of an ethylene copolymer having a lower MIE value than that of A), preferably a MIE value of less than 0.5 g / 10 min.
5. The polyethylene composition according to claim 1, which is obtainable by using a Ziegler-Natta polymerization catalyst in the polymerization stage.
6. The polyethylene composition of claim 5, wherein the Ziegler-Natta polymerization catalyst comprises the reaction product of: A) a solid catalyst component comprising Ti, Mg, chlorine and an internal electron donor ED selected from aliphatic monocarboxylic acid esters (EAA) and another internal electron donor ED selected from cyclic ethers (CE) I , the amount of the other internal donor is such that the EAA / CE molar ratio is from 0.02 to less than 20; B) an organo-Al compound; and optionally C) External electron donor compounds.
7. The polyethylene composition of claim 1 consisting of or comprising one or more ethylene copolymers.
8. The polyethylene composition of claim 1, having at least one of the following additional features: - an expansion ratio equal to or higher than 160%, in particular from 160% to 200%, - FNCT 6MPa / 50°C, equal to or higher than 40h, in particular from 40 to 100h; - a comonomer content equal to or lower than 1.7% by weight, in particular from 0.1 to 1.7% by weight, relative to the total weight of the composition; - MIP is 0.3 g / 10 min or more, more preferably 0.5 g / 10 min or more, in particular from 0.3 to 4 g / 10 min, or from 0.5 to 4 g / 10 min, wherein MIP is the melt flow index at 190° C. and a load of 5 kg, determined according to ISO 1133-12012-03; - (MIF / MIE) / ER ratio is between MIF / MIE and ER, equal to or less than 26, more preferably equal to or less than 25.5, in particular from 26 to 15, or from 25.5 to 15, or from 26 to 20, or from 25.5 to 20; - long chain branching index LCBI equal to or greater than 0.55, more preferably equal to or greater than 0.60, in all cases the upper limit is preferably 0.95; Wherein LCBI is the ratio of the measured mean square radius of gyration Rg measured by GPC-MALLS at a molecular weight of 1,000,000 g / mol to the mean square radius of gyration of a linear PE having the same molecular weight; -η 0.02 Equal to or greater than 56,000 Pa.s, in particular from 56,000 to 80,000 Pa.s; where η 0.02 is the complex viscosity of the melt, measured in a parallel-plate (or so-called plate-plate) rheometer in dynamic oscillatory shear mode with an applied angular frequency of 0.02 rad / s at a temperature of 190 °C; -(η 0.02 / 1000) / LCBI ratio in η 0.02 Divided by 1000 and between LCBI, from 85 to 150, preferably from 90 to 130; - HMWcopo index from 0.5 to 5, in particular from 0.5 to 3.5; Wherein the HMWcopo index is determined according to the following formula: HMWcopo=(η 0.02 x t maxDSC ) / (10^5) where t maxDSC It is the time (in minutes) required to reach the maximum value of the heat flow for crystallization (in mW) at a temperature of 124°C under static conditions (time to reach the maximum crystallization rate, equivalent to t1 / 2 the crystallization half-time), measured in isothermal mode in a differential scanning calorimeter DSC.
9. A process for preparing the polyethylene composition according to claim 1, The process comprises contacting a free radical initiator with a precursor polyethylene composition (I) having a MIF / MIE ratio of less than 1) and preferably equal to or less than 120, more preferably equal to or less than 115, in particular from 90 to 120 or from 90 to 115. I ) ratio; 1) / 1 I ) is a ratio of the MIF / MIE 1 of the final polyethylene composition (after contact with the free radical initiator) to the MIF / MIE 1 of the precursor polyethylene composition (I). I ), equal to or greater than 1.05, preferably equal to or greater than 1.1, in particular from 1.05 or from 1.1 to 1.8, or from 1.05 or from 1.1 to 1.
6.
10. The process according to claim 9, wherein the precursor polyethylene composition (I) has the following additional features: 2 I )MIF is from 30 to 50 g / 10 min, preferably from 35 to 45 g / 10 min; 3 I ) density from 0.948 to 0.960 g / cm 3 , especially from 0.950 to 0.958 g / cm 3 ; 4 I )ER value is from 2 to 5, preferably from 2 to 4.
5.
11. The process according to claim 9, which is carried out by contacting the free radical initiator with the precursor polyethylene composition (I) at a temperature of 180 to 350°C in an extruder device.
12. The process according to claim 9, wherein the free radical initiator is selected from organic peroxides.
13. A process according to claim 12, wherein the amount of one or more organic peroxides added corresponds to the content of initiator in the precursor polyethylene composition (I) and is from 10 to 100 ppm by weight, more preferably from 25 to 90 ppm by weight, and in particular from 25 to 80 ppm by weight.
14. The process of claim 12, wherein the one or more organic peroxides are selected from 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 3,6,9-triethyl-3,6,9-trimethyl-1,2,4,5,7,8-hexanone or representative 3,6,9-trimethyl-3,6,9-tri(alkyl)-1,2,4,5,7,8-hexanone wherein the alkyl radical is propyl or ethyl.
15. An article of manufacture comprising the polyethylene composition of claim 1.
16. An article of manufacture according to claim 15 in the form of a blow moulded article, in particular a handle article.
Citation Information
Patent Citations
Components and catalysts for the polymerization of olefins
EP0395083A2
Bimodal polyethylene compositions for blow molding applications
US20120220747A1
Processing polyethylene resins
US4603173A
Procedure for manufacturing catalyst components for polymerizing olefines
US4829034A
Process for producing a catalyst for olefin polymerization
US5100849A